Effect of Benralizumab in Patients With Severe Eosinophilic Asthma and Chronic Rhinosinusitis With Nasal Polyps: A Case Series. Issue 5 (September 2021) - Chitguppi, Chandala; Patel, Prachi; Gandler, Alan; Murphy, Kira; Khoury, MD, Tawfiq; Monostra, Pamela; Bork, Stephanie; Toskala, Elina; Rabinowitz, Mindy; Rosen, Marc; Nyquist, Gurston; Most, Jessica
Objective: To analyze the effect of benralizumab in severe eosinophilic asthma (SA) and chronic rhinosinusitis with polyps (CRSwP). Methods: Retrospective review of patients with both SA and CRSwP that were treated with benralizumab. Asthma controlled test (ACT), pulmonary function metrics (FEV1), Meltzer endoscopic polyp scores, SNOT-22 scores, were collected before and after at least 4 months of benralizumab therapy. Results: 23 patients were included. The mean age at the time of enrollment into benralizumab therapy was 50.47 ± 17.3 years and majority (65.2%, n = 15) were males. Pulmonary Effects: In comparison to baseline ACT, scores at four months showed significant improvement (p = 0.03). In those with pre and post spirometry measurements, mean FEV1 showed significant increase following benralizumab therapy (p = 0.04) with a mean increase of 547 mL ± 597 mL following therapy. Sinonasal Effects: 78.5% of subjects on benralizumab had a significant improvement in sinonasal symptoms (p = 0.009) based on their SNOT-22 scores. Additionally, there was an improvement in endoscopic polyp scores, although not statistically significant, following benralizumab therapy (p = 0.2) with 54.5% patients showing improvement. Conclusion: Usage of benralizumab in patients with SA and CRSwNP can lead to significantly improved asthma control, lung function, and sinonasal quality of life. Additionally, in this patient population, there was a subset of patients that showed a significant reduction in polyp burden.